Waffengleichheit im Vorverfahren Eine kritische Auseinandersetzung mit der konzeptionellen Ausgestaltung des Strafverfahrens in der Schweiz - Garland, Lorenz (sui generis, 2019)
The concept of equality of arms is often used in the context of criminal proceedings but is rarely defined clearly. The present work is preparing to give the term an outline. It highlights the historical roots of this important structural principle and shows the goals of equality of arms. The work pays particular attention to the case law of the European Court of Human Rights (ECHR). In the decisive evidence procedure, this requires a procedural balance between the accused person on the one hand and law enforcement authorities on the other. To what extent does Swiss procedural reality - with its postponement of crucial procedural steps in the pre-litigation - meet this demand? Based on empirical data, it is shown that the institutional superiority of law enforcement agencies in the underregulated preliminary proceedings has the potential to objectively restrict the defendant's rights of defense. The author discusses how this problem can be dealt with in a holistic view of the Swiss criminal trial using various variants.